SURVIVAL AFTER 100 YEARS OF AGE IN PORTUGUESE CENTENARIANS. (16th November 2018) - Teixeira, L; Araujo, L; Paul, C; Ribeiro, O
Abstract: The group of individuals aged 80 and over is growing faster than other segment of the population, and within this group the number of centenarians has risen exponentially worldwide. This phenomena lead to an increasing number of centenarian studies, improving the knowledge about this population, validating the idea of heterogeneity that characterizes this group. However, the factors influencing their aging survival remains understudied. The present study aims to identify factors associated with survival after 100 years old in a sample of Portuguese centenarians. After being included in a population-based study on centenarians (PT100–Oporto Centenarian Study), each participant was assessed by a telephone interview every 6 months in order to assess his/her health condition. Follow-up was considered as the time (in months) between 100th birthday and death or the last telephone contact. Survival analysis was performed to identify factors associated with survival after 100 years old. Sociological and medical factors were considered. 140 centenarians were assessed and 115 (82.1%) died. The median survival time after 100 years old was 38 months. Survival after age 100 was associated with acute disease (last month), self-perception of physical condition and drinking status. This study intends do identify factors that predict longevity in long-lived individuals. Findings recognize the importance of factors related with health status, self-perception of physical condition and life style (no alcohol consume) for survival. Further studies should explore the predictive value of these factors, as well as psychosocial aspects, considering living longer but also the quality of time beyond one hundred.